Minimally Invasive Microbiopsies as an Improved Sampling Method for the Diagnosis of Cutaneous Leishmaniasis. (17th August 2020) - Churiso, Gemechu; van Henten, Saskia; Cnops, Lieselotte; Pollmann, Julia; Melkamu, Roma; Lemma, Mulualem; Kiflie, Amare; Fikre, Helina; van Griensven, Johan; Adriaensen, Wim
Abstract: Current sampling methods to diagnose cutaneous leishmaniasis are invasive and painful. An alternative and minimally invasive microbiopsy device was evaluated in a diverse range of cutaneous leishmaniasis lesions in Ethiopia. Using polymerase chain reaction–based diagnosis, the microbiopsy outperformed the routine skin slit sample by detecting more patients while pain scores were significantly lower. Abstract : Current sampling methods to diagnose cutaneous leishmaniasis are invasive and painful. In diverse lesion types and using PCR-based diagnosis, a novel and minimally-invasive microbiopsy outperformed the routine skin slit sample by detecting more patients while pain scores were significantly lower.